PERAN OLAHRAGA DALAM PROMOSI KESEHATAN MENURUT PERATURAN PERUNDANG-UNDANGAN - Rizky Yosa Adhi Prabowo; Gunawan Widjaja (Cross-border, 2022)
Sport as a physical activity that is part of the Healthy Living Community Movement aims to improve the health status of individuals and the community through promotive and preventive health efforts, therefore this paper wants to discuss the extent of the role of sport in health promotion when viewed from the laws and regulations. . This paper uses a normative legal research method on legal principles which, when viewed from its nature, is descriptive research, from its form it is prescriptive research, from its purpose is problem solution research and from its application including applied research with the data used is secondary data based on the literature or has been available. The conclusions obtained in this paper are Law Number 36 of 2009 concerning Health, Law Number 3 of 2005 concerning the National Sports System has regulated the implementation of health and sports promotion, but since 2017 there has been Presidential Instruction Number 1 of 2017 concerning Movement Healthy Living Community that synergizes all sports activities and health promotions to achieve the highest degree of health.